Investigation on phosphate transport mechanisms in laterite and laterite clay soils and its immobilization: Mining region - B. Bincy; C.P. Devatha; Arun Kumar Thalla (Case Studies in Chemical and Environmental Engineering, 2025)
Phosphate contamination from mining regions has significantly affected soil strata and groundwater quality. This study examines the transport mechanisms and adsorption behaviour of phosphate in laterite soil (LS) and laterite clay soil (LCS) and the effectiveness of various laterite clay mixtures (LCM)— bentonite (LB), kaolinite (LK), and zeolite (LZ)—in enhancing its adsorption and immobilization. The survey indicated that 60 % of wells were no longer used due to chemical contamination (66 %) and acid leakage (34 %). Additionally, 82 % of people rely on industry-supplied water for drinking, emphasizing the impact of contamination on well usability. A 3D unconfined aquifer model, incorporating LS and LCS soil basins, field-equivalent soil properties, and well conditions, was used to analyse phosphate transport under real-world conditions. The aquifer model indicated a gradual increase in phosphate concentration within wells, peaking at 6.50 ppm and 5.60 ppm in wells 2 and 3, respectively. Batch adsorption, XRD, and SEM analysis were performed to study the adsorption kinetics and surface morphology of LS and LCS under varying concentrations. Findings show that LCS has a higher adsorption capacity than LS (Kd-187.10, 2.40 L/kg, and KL -290.77, 22.32 L/kg), and Freundlich adsorption isotherm (FRI) further confirmed it (Kf-158.69 and 16.80 L/kg). Immobilization analyses showed that the LB mixture exceeded LK and LZ, with a maximum adsorption capacity (Kf) of 86.5 L/kg compared to kaolinite (71.4 L/kg) and zeolite (49.9 L/kg). The findings emphasize bentonite as the most suitable for contaminant immobilization with laterite soils in the study area.